ln(6)+ln(x-6)=ln(x)

Simple and best practice solution for ln(6)+ln(x-6)=ln(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(6)+ln(x-6)=ln(x) equation:


Simplifying
ln(6) + ln(x + -6) = ln(x)

Reorder the terms for easier multiplication:
6ln + ln(x + -6) = ln(x)

Reorder the terms:
6ln + ln(-6 + x) = ln(x)
6ln + (-6 * ln + x * ln) = ln(x)
6ln + (-6ln + lnx) = ln(x)

Combine like terms: 6ln + -6ln = 0
0 + lnx = ln(x)
lnx = ln(x)

Multiply ln * x
lnx = lnx

Add '-1lnx' to each side of the equation.
lnx + -1lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
0 = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6=16t^2+31+4 | | 4=16t^2+31+6 | | H=16t^2+31+6 | | log3-3=1/27 | | 3-3=1/27 | | 5x+7=6x+2(2) | | 1.2=6(4-0.4g)-4.8 | | 2x+1=-(x-13) | | 75/925 | | -3.8x-5=-2.9x+4 | | G(-1)=-2y+2 | | 1/4d-1=7 | | 8+8=-16 | | G(-2)=-3x+8 | | 7/9y-4 | | 3=4(x-7)+2(10-x) | | 4x^3-48x^2+144x+9=0 | | (2/5)(10/2)= | | 9x^3-27x/18x^2 | | 5c-1=5c+6c | | 3.8/x^2=0.7 | | -1=-4t+2r | | -x^2+8.5x+4=0 | | (a^1/2b^1/3)^1/2 | | .3(11x+4)=2.1-(x+8) | | 18-2x=6x+3 | | 9(k+3)+2=11(k-y) | | x^2=81/121 | | (3x-4)(4-2x)=0 | | .7(7x+3)=1.8-(x+9) | | -x+6=-2x-12 | | -(3/x)=9 |

Equations solver categories